Дениска и его друзья - Драгунский Виктор Юзефович (Серия "Любимые книги детства", 2019)
Экземпляры: ф.14 (20220504) / Инвентарный номер: 63684 / Цена: 40.00 / Авт.знак: Д 72 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6